2015
DOI: 10.1116/1.4919610
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interactions between cold atmospheric plasma and skin-components with vibrational microspectroscopy

Abstract: Using infrared and Raman microspectroscopy, the authors examined the interaction of cold atmospheric plasma with the skin's built-in protective cushion, the outermost skin layer stratum corneum. Following a spectroscopic analysis, the authors could identify four prominent chemical alterations caused by plasma treatment: (1) oxidation of disulfide bonds in keratin leading to a generation of cysteic acid; (2) formation of organic nitrates as well as (3) of new carbonyl groups like ketones, aldehydes and acids; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
(44 reference statements)
3
14
0
Order By: Relevance
“…43,44 In this context, it was hypothesized that NO penetration into the skin may be a possible mechanism for plasma-induced changes of microcirculation. 27,45,46 In general, for diCAP treatment durations of 90 seconds, 180 seconds, and 270 seconds, respectively, we observed a more pronounced impact on microcirculatory parameters with increasing treatment time indicated by an absolute increase in significance levels.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…43,44 In this context, it was hypothesized that NO penetration into the skin may be a possible mechanism for plasma-induced changes of microcirculation. 27,45,46 In general, for diCAP treatment durations of 90 seconds, 180 seconds, and 270 seconds, respectively, we observed a more pronounced impact on microcirculatory parameters with increasing treatment time indicated by an absolute increase in significance levels.…”
Section: Discussionmentioning
confidence: 62%
“…This general trend is well known for CAP generated in air and it is attributed to reactions of plasma‐generated gaseous species (reactive oxygen and nitrogen species—RONS) with omnipresent H 2 O, which lead to the formation of nitrous acid, nitric acid, and hydrogen peroxide . In this context, it was hypothesized that NO penetration into the skin may be a possible mechanism for plasma‐induced changes of microcirculation …”
Section: Discussionmentioning
confidence: 92%
“…Raman imaging of solid tissue samples enabled the simultaneous generation of morphological and biochemical information after tissue treatment. This is a great advantage compared to previous studies, which aimed to analyze plasma's effects on lipids in the outermost skin layer of keratinized epithelium by Raman microspectroscopy [43]. Further studies demonstrated the ability of Raman spectroscopy to identify plasma-driven changes in lipids and lipid droplets (composed of phospholipids and triglycerides) in bacterial spores, budding-yeast and HeLa cells [44].…”
Section: Discussionmentioning
confidence: 97%
“…However, our findings indicate that other factors produced by CAP, such as nitric oxide (NO) or electric fields and currents, may also play a major role in the effect of CAP on superficial soft tissue. NO is typically produced by the cell's nitric oxide synthase (NOS) as an endogenous gas with various physiological effects, but it is also created in the field of CAP (Kartaschew et al, 2015;García-Alcantara et al, 2013;Heuer et al, 2015). NO acts as a vasodilator.…”
Section: Discussionmentioning
confidence: 99%